Metabolic Rewiring in Glioblastoma Cancer: EGFR, IDH and Beyond - El Khayari, Abdellatif; Bouchmaa, Najat; Taib, Bouchra; Wei, Zhiyun; Zeng, Ailiang; El Fatimy, Rachid (Frontiers in Oncology, 2022)
Glioblastoma multiforme (GBM), a highly invasive and incurable tumor, is the humans' foremost, commonest, and deadliest brain cancer. As in other cancers, distinct combinations of genetic alterations (GA) in GBM induce a diversity of metabolic phenotypes resulting in enhanced malignancy and altered sensitivity to current therapies targeting its metabolic reprogramming (MR). Interestingly, dysregulated cell metabolism in GBM has been recently linked to the acquired GA. In this work, we captured the current knowledge of genetic alterations in GBM, provided a detailed understanding of the alterations in metabolic pathways, and discussed their relevance in GBM therapy. We also analyzed associations and co-expression, differential gene expression (DGE), gene ontology (GO), and gene set enrichment analysis (GSEA) using the Cancer Genome Atlas (TCGA) database. c-MYC, HK1, and HK2 were lowly expressed in EGFR-altered samples and negatively correlated with EGFR mRNA levels. DGE analysis revealed 86 significantly upregulated genes in GBM samples harboring EGFR alterations (FC >2; Adj-p <0.05). These genes were enriched in fluid transport, leukotriene metabolism, and aromatic amino acids. Similarly, amino acids metabolism (AAM), especially non-essential amino acids, was distinguished as an enriched pathway in KEGG. Furthermore, oxidative phosphorylation (OXPHOS) pathways were essentially upregulated in EGFR-altered GBMs, whereas glycolysis and MYC targets pathways were negatively enriched. Our results suggest that EGFR changes may conduce to metabolic rewiring by acting on several metabolic aspects, principally, through adaptative modulation of OXPHOS and AAM, in addition to improvement of fluid uptake and cellular homeostasis.